El libro del ombligo! - Boynton, Sandra; McMullan, John (Teacher); Cuellar, Lourdes (Nueva York : Workman Publishing, 2019)
Hippopotamuses celebrate their belly buttons.
Keywords: Belly button -- Juvenile fiction; Hippopotamus -- Juvenile fiction; Spanish language materials; Board books